A prospective cohort study comparing the reactogenicity of trivalent influenza vaccine in pregnant and non-pregnant women - Regan, Annette; Tracey, L.; Blyth, C.; Mak, D.; Richmond, P.; Shellam, G.; Talbot, C.; Effler, P. (BioMed Central Ltd, 2015)
Background: Influenza vaccination during pregnancy can prevent serious illness in expectant mothers and provide protection to newborns; however, historically uptake has been limited due to a number of factors, including safety concerns. Symptomatic complaints are common during pregnancy and may be mistakenly associated with reactions to trivalent influenza vaccine (TIV). To investigate this, we compared post-vaccination events self-reported by pregnant women to events reported by non-pregnant women receiving TIV. Methods: A prospective cohort of 1,086 pregnant women and 314 non-pregnant female healthcare workers (HCWs) who received TIV between March-May 2014 were followed-up seven days post-vaccination to assess local and systemic adverse events following immunisation (AEFIs). Women were surveyed by text message regarding perceived reactions to TIV. Those reporting an AEFI completed an interview by telephone or mobile phone to ascertain details. Logistic regression models adjusting for age and residence were used to compare reactions reported by pregnant women and non-pregnant HCWs.Results: Similar proportions of pregnant women and non-pregnant, female HCWs reported ≥1 reaction following vaccination with TIV (13.0% and 17.3%, respectively; OR = 1.2 [95% CI: 0.8-1.8]). Non-pregnant, female HCWs were more likely to report fever or headache compared to pregnant women (OR: 4.6 [95% CI 2.1-10.3] and OR: 2.2 [95% CI 1.0-4.6], respectively). No other significant differences in reported symptoms were observed. No serious vaccine-associated adverse events were reported, and less than 2% of each group sought medical advice for a reaction. Conclusions: We found no evidence suggesting pregnant women are more likely to report adverse events following influenza vaccination when compared to non-pregnant female HCWs of similar age, and in some cases, pregnant women reported significantly fewer adverse events. These results further support the safety of TIV administered in pregnant women.